The validity and reliability of GPS units for measuring distance in team sport specific running patterns - Jennings, D.; Cormack, S.; Coutts, A. J.; Boyd, L.; Aughey, R. J. (International Journal of Sports Physiology and Performance, 2010)
Purpose: To assess the validity and reliability of distance data measured by global positioning system (GPS) units sampling at 1 and 5 Hz during movement patterns common to team sports. Methods: Twenty elite Australian Football players each wearing two GPS devices (MinimaxX, Catapult, Australia) completed straight line movements (10, 20, 40 m) at various speeds (walk, jog, stride, sprint), changes of direction (COD) courses of two different frequencies (gradual and tight), and a team sport running simulation circuit. Position and speed data were collected by the GPS devices at 1 and 5 Hz. Distance validity was assessed using the standard error of the estimate (±90% confidence intervals [CI]). Reliability was estimated using typical error (TE) ± 90% CI (expressed as coefficient of variation [CV]). Results: Measurement accuracy decreased as speed of locomotion increased in both straight line and the COD courses. Difference between criterion and GPS measured distance ranged from 9.0% to 32.4%. A higher sampling rate improved validity regardless of distance and locomotion in the straight line, COD and simulated running circuit trials. The reliability improved as distance traveled increased but decreased as speed increased. Total distance over the simulated running circuit exhibited the lowest variation (CV 3.6%) while sprinting over 10 m demonstrated the highest (CV 77.2% at 1 Hz). Conclusion: Current GPS systems maybe limited for assessment of short, high speed straight line running and efforts involving change of direction. An increased sample rate improves validity and reliability of GPS devices.